2004
DOI: 10.1007/s00418-004-0627-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific and developmentally regulated expression of the AE1 anion exchanger in the chicken chorioallantoic membrane

Abstract: Antibodies specific for the chicken AE1 anion exchanger have been used to determine the cell-type specific pattern of expression of this electroneutral transporter in the chick chorioallantoic membrane (CAM) during embryonic development. Immunolocalisation analyses demonstrated that the AE1 anion exchanger accumulated in the basolateral membrane of a subset of cells in both the chorionic and allantoic epithelial layers. Double immunostaining indicated that the AE1-positive cells in the chorionic and allantoic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Furthermore, VC cells are also important for the acid-base balance of the embryo. To carry out these functions, VC cells contain high concentrations of carbonic anhydrase CAII (Anderson et al 1981;Gabrielli et al 2001;Tuan 1980), vacuolar-type H + -AT Pase (Narbaitz et al 1995), and anion exchanger-1, which is accumulated in the basolateral plasma membrane domain (Gabrielli et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, VC cells are also important for the acid-base balance of the embryo. To carry out these functions, VC cells contain high concentrations of carbonic anhydrase CAII (Anderson et al 1981;Gabrielli et al 2001;Tuan 1980), vacuolar-type H + -AT Pase (Narbaitz et al 1995), and anion exchanger-1, which is accumulated in the basolateral plasma membrane domain (Gabrielli et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Note how SMA Wlaments are arranged approximately at right angles to DES, and thus extend into the pillar core, whereas DES outlines the axial direction of the loops. Note that not all, but only erythrocyte nuclei were included, with six of them encircling the pillar, to better illustrate the capillary lumen ent epithelial cell types (Gabrielli et al 2003(Gabrielli et al , 2004Matschke et al 2006), but were not used here. Instead, all chorionic epithelial cells were deWned as unstained by any of the applied markers (except YoPro-1), and their position.…”
Section: Desmin and Sma Expression In The Mature Cammentioning
confidence: 99%
“…The specialization panel of the VC cells has then been enriched by data from our subsequent investigations: a developmentally-regulated and cell type-specific expression of AE1 anion exchanger, the electroneutral transporter which mediates the exchange of Cl − for HCO 3 − across the cell plasma membrane in a wide variety of cell types [69], was demonstrated for the first time in the CAM epithelia [30]. In the chorionic epithelium, AE1 was restricted to the basolateral membranes of the VC cells which, at electron microscopic analysis, clearly showed that AE1 specifically accumulates in extensive projections extending from the lateral membrane of VC cells towards the adjacent CC cells (Figure 5(a)).…”
Section: Transepithelial Ion Transport In the Cam Meets Multiple Fmentioning
confidence: 99%
“…In the chorionic epithelium, AE1 was restricted to the basolateral membranes of the VC cells which, at electron microscopic analysis, clearly showed that AE1 specifically accumulates in extensive projections extending from the lateral membrane of VC cells towards the adjacent CC cells (Figure 5(a)). The basolateral membranes of the adjacent CC cells as well as the apical membranes of both CC cells and VC cells were always unlabelled [30]. …”
Section: Transepithelial Ion Transport In the Cam Meets Multiple Fmentioning
confidence: 99%